2013
DOI: 10.1074/jbc.m112.438846
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Transcription Factor GLI1 Identifies a Signaling Network in the Tumor Microenvironment Mediating KRAS Oncogene-induced Transformation

Abstract: Background: KRAS is a known oncogene driving transformation in multiple tissues. Results: We demonstrate a role for the transcription factor GLI1 in KRAS-induced transformation through regulation of the IL-6/STAT3 axis in the tumor microenvironment. Conclusion: This study defines a novel oncogenic network downstream of KRAS modulating transformation. Significance: This knowledge will contribute to the understanding of the pathogenesis of tumors driven by KRAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
89
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 38 publications
(55 reference statements)
5
89
0
1
Order By: Relevance
“…This transcription factor is expressed at low levels in normal adult tissue, but it is often re-expressed and de-regulated in many human cancers carrying signature mutations in the Kras gene (10 -13). Recently, we demonstrated that the loss of GLI1 in a genetically engineered mouse model (GEMM) blocks the progression of pancreatic intraepithelial neoplasms (PanIN) induced by oncogenic KRAS (10). In agreement with these findings, using a transgenic model overexpressing a repressor form of the transcription factor GLI3 to antagonize GLI1 activity, Rajurkar et al (11) showed a requirement for this transcription factor in pancreatic cancer initiation.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…This transcription factor is expressed at low levels in normal adult tissue, but it is often re-expressed and de-regulated in many human cancers carrying signature mutations in the Kras gene (10 -13). Recently, we demonstrated that the loss of GLI1 in a genetically engineered mouse model (GEMM) blocks the progression of pancreatic intraepithelial neoplasms (PanIN) induced by oncogenic KRAS (10). In agreement with these findings, using a transgenic model overexpressing a repressor form of the transcription factor GLI3 to antagonize GLI1 activity, Rajurkar et al (11) showed a requirement for this transcription factor in pancreatic cancer initiation.…”
supporting
confidence: 58%
“…Immunohistochemistry-Paraffin-embedded tissue sections were processed using methods described previously (10). Primary antibodies used are as follows: CK19 (TROMA III, Developmental Studies Hybridoma Bank, Iowa City, IA); PCNA (Abcam, Cambridge, MA); F4/80 (Abcam), and CD31 (Santa Cruz Biotechnology).…”
Section: G12dmentioning
confidence: 99%
See 2 more Smart Citations
“…Constitutive activation of the STAT3 pathway has been noted in a wide range of cancers and typically occurs in response to stimulation by tumor-promoting factors, including epidermal growth factor, IL-6, Tyr kinase, and many others (21,22). Inhibition of aberrantly activated STAT3 signaling pathway may present a novel antitumor strategy (Fig.…”
Section: Discussionmentioning
confidence: 99%